2012
DOI: 10.4304/jcp.7.12.2979-2986
|View full text |Cite
|
Sign up to set email alerts
|

Tag Ontology Automatic Building for Semantic Searching of Services: a Case Study on Mashup Services

Abstract: The explosion of services like web services, APIs, Mashups, etc., makes how to find the right one you need a tough problem. Tags, as a kind of metadata have been widely used to annotate services. In this paper, we propose to use an ontology automatically built from tags to improve the performance of service searching. We use the famous Mashup directory, Programmable.com, to illustrate our approach: First, all metadata especially tags of mashups and APIs at Programmable.com are crawled and preprocessed by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…W P. Pan focused on the building of a tag ontology to enhance the semantic searching of services, and final to tackle this problem. By this method, we improved the efficiency of searching the corresponding service [21]. The framework of PPHIIS is based on MDA (Model Driver Architecture), and is designed in view of the framework needs and the advantage of characteristics of the organization agent.…”
Section: Methodsmentioning
confidence: 99%
“…W P. Pan focused on the building of a tag ontology to enhance the semantic searching of services, and final to tackle this problem. By this method, we improved the efficiency of searching the corresponding service [21]. The framework of PPHIIS is based on MDA (Model Driver Architecture), and is designed in view of the framework needs and the advantage of characteristics of the organization agent.…”
Section: Methodsmentioning
confidence: 99%
“…Blitzer et al [8] investigate domain adaptation for sentiment classifiers, focusing on online reviews for different types of products. Prabowo and Thelwall [9] conducted experiments on movie reviews, product reviews and Myspace comments by combining a rule-based classifier and supervised learning algorithm, and found that the hybrid classification showed an improvement in accuracy. Machine learning approaches work well in situations where large labeled corpora are available for training and validation [10].…”
Section: Related Workmentioning
confidence: 99%
“…The ontology is a formal knowledge representation method to facilitate human and computer interactions and it can be expressed by using formal semantic markup languages such as RDF and OWL [1]. And in particular, domain ontology constructs the relationship among domain concepts and helps in determining the structure of knowledge [2].…”
Section: Introductionmentioning
confidence: 99%